2014
DOI: 10.1111/eci.12375
|View full text |Cite
|
Sign up to set email alerts
|

Reduced circulating levels of TWEAK are associated with Gestational Diabetes Mellitus

Abstract: sTWEAK concentrations are lower in patients with GDM compared with healthy pregnant women, and low concentrations of sTWEAK are associated with insulin resistance. These findings suggest that insulin resistance during pregnancy is closely linked to inflammatory imbalance and sTWEAK may represent a new candidate associated with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(53 reference statements)
3
10
1
Order By: Relevance
“…As circulating sCD163 levels have been shown to correlate with CD163 expression, macrophage content, and insulin sensitivity in adipose tissue, we speculate that early activation of monocytes/macrophages and infiltration in adipose tissue may be an important event in the early development of GDM, at least in a subgroup of women with increased body mass. The association between sCD163 and insulin resistance at 30 to 32 weeks, as also observed in the above GDM studies, may suggest a role for sCD163 and monocyte/macrophage activations in the normal adaption of insulin resistance in later pregnancy. Thus, our findings may reflect that macrophages exert distinct effects depending on the presence of adiposity, hyperglycaemia, and inflammation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As circulating sCD163 levels have been shown to correlate with CD163 expression, macrophage content, and insulin sensitivity in adipose tissue, we speculate that early activation of monocytes/macrophages and infiltration in adipose tissue may be an important event in the early development of GDM, at least in a subgroup of women with increased body mass. The association between sCD163 and insulin resistance at 30 to 32 weeks, as also observed in the above GDM studies, may suggest a role for sCD163 and monocyte/macrophage activations in the normal adaption of insulin resistance in later pregnancy. Thus, our findings may reflect that macrophages exert distinct effects depending on the presence of adiposity, hyperglycaemia, and inflammation.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, they detected increased staining of CD163 in placental tissue, presumably from placental macrophages as well as increased secretion from placental explants suggesting the placenta as an alternative source of increased sCD163 in GDM, although this would have less impact in early pregnancy. The non‐significant increase in sCD163 in another study of 66 GDM and 71 control women at 27 weeks of gestation could partly be related to the relative late sampling. Furthermore, at 14 to 16 weeks, high sCD163 was associated with poorer β‐cell function but only in individuals with high BMI as also observed in T2DM .…”
Section: Discussionmentioning
confidence: 92%
“…In the literature, there are contradictory findings of the relationship between TWEAK levels and atherosclerosis (27,28). Previous studies showed a negative relationship between serum TWEAK levels and coronary artery disease, cIMT, insulin resistance, gestational diabetes and type II diabetes (29)(30)(31)(32). However, studies cannot explain the reason why atherosclerotic process accelerated when serum TWEAK levels were low (33).…”
Section: Discussionmentioning
confidence: 99%
“…There are not many studies on the relationship between pregnancy related diseases and sTWEAK in the literature. Recently Simón-Muela et al showed decreased sTWEAK levels in patients with gestational diabetes compared to control subjects [ 27 ]. The authors related their finding to decreased insulin sensitivity, consistent with the previous report of Kralisch et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%